2019
DOI: 10.17015/ejbe.2019.024.01
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Economic Growth, Energy Consumption and Carbon Dioxide Emissions: Evidence from Central Asia

Abstract: This article aims to explore the relationship between economic growth, energy consumption and CO2 emissions of five Central Asian countries between 1998 and 2017. We found that per capita energy consumption has a positive relationship with per capita GDP, while per capita CO2 emissions negatively affect per capita GDP in Central Asia. Further, per capita GDP has a negative impact on per capita energy consumption in the region. Results reflect that the economic growth of Central Asian countries still heavily de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 16 publications
(19 reference statements)
0
6
0
Order By: Relevance
“…e preceding literature also shows the relationship of energy consumption, renewable energy consumption, and carbon emission. For instance, [28] have explored the determinants of carbon emission in developing countries where their results illustrate that economic growth and energy consumption are affecting carbon emission positively in South East Asia. ey further state that carbon emission is higher in Indonesia and Vietnam than other countries in the region.…”
Section: Energy Consumption and Carbon Emissionmentioning
confidence: 99%
“…e preceding literature also shows the relationship of energy consumption, renewable energy consumption, and carbon emission. For instance, [28] have explored the determinants of carbon emission in developing countries where their results illustrate that economic growth and energy consumption are affecting carbon emission positively in South East Asia. ey further state that carbon emission is higher in Indonesia and Vietnam than other countries in the region.…”
Section: Energy Consumption and Carbon Emissionmentioning
confidence: 99%
“…If there is an increase in economic growth then there is a decrease in employment. Contrary to the study of Nguyen (2019) stating that CO2 emissions have negative impact on economic growth and CO2 emissions should be reduced because it has been defined as a determinant leading to a decrease in economic growth. Table 3 shows the cointegration results for Japan indicating that the variables are cointegrated in the long-run.…”
Section: Resultsmentioning
confidence: 81%
“…Economic growth was supported in Singapore and Thailand for the long run which supports the Environmental Kuznets Curve (EKC) hypothesis. Ejuvbekpokpo (2014), Kasperowicz (2015) and Nguyen (2019) revealed that CO2 emissions have negative impact on economic growth. CO2 emissions should be reduced because it has been defined as a determinant leading to a decrease in economic growth.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…The unconventional approach of processing plastic waste at incineration and landfill sites is no longer sustainable [5]. This is due to the high emissions of toxic gases, including carbon dioxide (CO 2 ), into the atmosphere, thereby increasing global temperatures and climatic conditions [6].…”
Section: Eco-friendly Techniques To Transform Waste Into Valuable Products In a Sustainable Environmentmentioning
confidence: 99%
“…It is further estimated that the importation of plastics to the continent would likely double in the next five years, contributing to the rise in world's temperature significantly [4]. World's temperature is also projected to increase from 1.5 to 3 °C with a corresponding impact on food insecurity, water supply, inequality, and poverty [5].…”
Section: Introductionmentioning
confidence: 99%